Peace Development Training for Teachers as Peace Educators in Supporting Merdeka Belajar - Eliasa, Eva Imania; Lidyasari, Aprilia Tina; Nurmalasari, Yuli; Mutmainah, Mutmainah (Journal of Educational Science and Technology (EST), 2023)
This research aims to develop the capacity for peace among school counselors in implementing Merdeka Belajar. The findings reveal that teachers need improvement in understanding concepts and skills for peace which are assumed to be beneficial for themselves and the school. The research uses a quantitative approach with a quasi-experimental one-group pretest posttest design.  Participants in the study used convenient samples, 29 teachers of guidance and counseling at the Kulonprogo Junior High School. The training was divided into five sessions brainstorming, games, role playing, cinema therapy, and worksheet. The instrument used is the Peace Capacity Building Scale. Data analysis using t-test and ANOVA. Results show an increase in aspects of knowledge and skills. In addition, participants revealed that training is very important to be applied in the classroom and school. There are two outcomes achieved, namely the implementation agreement and articles published in journals.